2008
DOI: 10.1080/17496890802221357
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship education in Lesotho secondary schools: pedagogical challenges

Abstract: The paper explores the extent to which the entrepreneurship education component of the business education curriculum in Lesotho secondary education is being implemented. The study was undertaken in 18 schools during 1998, 1999 and 2000. Different research methods such as video recording, interviews and document analysis were used.Results indicate that teachers mainly employ didactic methods of teaching, leaving little room for entrepreneurship development. This is reinforced by the type of examination question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…The new methods should therefore put the learners at the forefront as knowledge constructors. In this way, the CAP challenges the dominant teacher-centred methodologies found to be prevalent in Lesotho classrooms (Nketekete & Motebang, 2008). The current study revealed that the participants lacked knowledge and skills to supervise the enactment of learner-centred pedagogy.…”
Section: Leading the Unexplained Pedagogymentioning
confidence: 71%
See 1 more Smart Citation
“…The new methods should therefore put the learners at the forefront as knowledge constructors. In this way, the CAP challenges the dominant teacher-centred methodologies found to be prevalent in Lesotho classrooms (Nketekete & Motebang, 2008). The current study revealed that the participants lacked knowledge and skills to supervise the enactment of learner-centred pedagogy.…”
Section: Leading the Unexplained Pedagogymentioning
confidence: 71%
“…The radical changes envisaged by the CAP challenge the status quo by assigning new roles to teachers and principals in schools. For instance, education in Lesotho is said to be highly teacher-centred (Nketekete & Motebang, 2008). It was therefore necessary for the MoET to re-skill the core curriculum implementers to realise learner-centred teaching and…”
Section: Introductionmentioning
confidence: 99%
“…It also implies a particular view of knowledge and new roles for teachers and learners in the context of the Lesotho education system, which has been characterised historically by teacher-dominated methods (Mokuku, Jobo, Raselimo, Mathafeng, & Stark, 2005;Nketekete & Motebang, 2008).…”
Section: The Leesp Curriculum Intentionsmentioning
confidence: 99%
“…Entre las razones por las que esta competencia es poco desarrollada en la Educación Primaria, destaca el hecho de que dicha competencia no es propia de ninguna asignatura en concreto, como puede ocurrir, por ejemplo, en el caso de la competencia en comunicación lingüística, sino transversal a todas ellas (MITC, 2010;Peña et al, 2015). Por este motivo, el desarrollo de esta competencia recae fundamentalmente en los tutores por ser quienes más horas imparten al grupo-clase, los cuales necesitan tanto formación permanente sobre cómo fomentar esta competencia, como el apoyo de personal técnico especializado que facilite la elaboración de recursos adaptados al contexto del centro escolar, ya que en la mayoría de las ocasiones no se utilizan las metodologías idóneas para promover el emprendimiento en el aula (Bernal y Cárdenas, 2017;Nketekete y Motebang, 2008;Ruskovaara y Pihkala, 2013).…”
Section: Introductionunclassified